Framing Religious Pluralism as Deviation: A Digital Hadith-Based Discourse of Salafism on Instagram - Billah, Rodina; Zamzami, Mukhammad; Hegazy, Wael; Lutfi, Muhammad (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2025)
Digital transformation has changed the landscape of Islamic da'wah in Indonesia, including in the production and dissemination of exclusive religious discourse by Salafi groups. This study analyzes the Instagram account @ittiba_salaf, which consistently frames religious pluralism as a deviation from Islamic creed, by referring to verses of the Qur’an and hadith. This study uses Robert M. Entman's framing analysis approach, which includes four main elements—problem definition, cause diagnosis, moral evaluation, and solution recommendation—combined with  Maʿānī al-Ḥadīth analysis to reveal the ideological instruments underlying the use of hadith. The findings show that this account constructs pluralism as a theological and ideological threat, associated with Western liberalism and categorized as a form of kufr. This narrative represents theological reductionism that ignores the complexity of Indonesia’s pluralistic society. This study emphasizes that digital da'wah not only conveys religious messages, but also becomes an arena for contestation over the meaning and authority of Islam, requiring a moderate hermeneutical approach to bridge theological commitments with the reality of societal diversity.